2020
DOI: 10.1016/j.cell.2020.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-6 Is a Key Regulator of Innate Immunity, Inflammasome Activation, and Host Defense

Abstract: Highlights d Caspase-6 is required for innate immunity and ZBP1-NLRP3 inflammasome activation d Caspase-6 promotes ZBP1-mediated pyroptosis, apoptosis, and necroptosis (PANoptosis) d Caspase-6 binds RIPK3 and enhances the interaction between RIPK3 and ZBP1 d Mice deficient in caspase-6 were more susceptible to IAV infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
352
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 345 publications
(356 citation statements)
references
References 75 publications
3
352
1
Order By: Relevance
“…[46][47][48][49][50][51][52][53][54] Of note, NLRP3 inflammasome activation by influenza A virus (IAV) infection is regulated by the Z-DNA binding protein 1 (ZBP1)-containing PANoptosome, a recently identified multi-protein complex that senses IAV and controls induction of pyroptosis, apoptosis, and necroptosis in IAV-infected cells. 55 TAK1 inhibition and a host of additional microbial pathogens also induce NLRP3 inflammasome-mediated pyroptosis concomitant with induction of necroptosis and extrinsic apoptosis in the targeted cell population, a process that was recently coined as PANoptosis. [56][57][58][59] Moreover, gain-of-function mutations in NLRP3 cause autosomal dominantly inherited autoinflammatory diseases that are collectively named Cryopyrin-Associated Periodic Syndrome (CAPS), and which comprise-in increasing order of clinical severity-familial F I G U R E 1 Overview of different inflammasome complexes: (From left to right) Engagement of different TLR receptors leads to activation of IKKs, which in turn results in activation of NF-κB signaling.…”
Section: Nlrp3mentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53][54] Of note, NLRP3 inflammasome activation by influenza A virus (IAV) infection is regulated by the Z-DNA binding protein 1 (ZBP1)-containing PANoptosome, a recently identified multi-protein complex that senses IAV and controls induction of pyroptosis, apoptosis, and necroptosis in IAV-infected cells. 55 TAK1 inhibition and a host of additional microbial pathogens also induce NLRP3 inflammasome-mediated pyroptosis concomitant with induction of necroptosis and extrinsic apoptosis in the targeted cell population, a process that was recently coined as PANoptosis. [56][57][58][59] Moreover, gain-of-function mutations in NLRP3 cause autosomal dominantly inherited autoinflammatory diseases that are collectively named Cryopyrin-Associated Periodic Syndrome (CAPS), and which comprise-in increasing order of clinical severity-familial F I G U R E 1 Overview of different inflammasome complexes: (From left to right) Engagement of different TLR receptors leads to activation of IKKs, which in turn results in activation of NF-κB signaling.…”
Section: Nlrp3mentioning
confidence: 99%
“…We very recently discovered that the host factor caspase-6, the physiological role of which has been enigmatic for decades, acts as a ZBP1-NLRP3 inflammasome regulator (Figure 3). 54 We found that loss of caspase-6 in BMDMs leads to reduced ZBP1-NLRP3 inflammasome activation following IAV infection. 54 The reduced ZBP1-NLRP3 inflammasome assembly is not due to defective priming, since the activation of both NF-κB and pERK is not dampened.…”
Section: Irf1 Expression During Iav Infection Is Largely Dependent Onmentioning
confidence: 73%
“…54 We found that loss of caspase-6 in BMDMs leads to reduced ZBP1-NLRP3 inflammasome activation following IAV infection. 54 The reduced ZBP1-NLRP3 inflammasome assembly is not due to defective priming, since the activation of both NF-κB and pERK is not dampened. 54 Additionally, the induction of ZBP1 expression in Casp6 -/cells is normal following IAV infection.…”
Section: Irf1 Expression During Iav Infection Is Largely Dependent Onmentioning
confidence: 73%
See 2 more Smart Citations